PENGARUH MOTIVASI, DISIPLIN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA ASN POLRES SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Oktaviyanti, Yeni; Sari, Lita Permata; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2024)
The Indonesian National Police (Polri) is one of the law enforcement agencies that plays an important role in the country. The State Civil Apparatus of The Indonesian National Police who serve as administrative staff within the Polri environment are required to have high discipline and loyalty to the organization and leadership. The aim of this research is to analyze and test the influence of motivation, work discipline and leadership on the performance of the State Civil Apparatus of Situbondo Resort Police through job satisfaction. This research refers to explanatory research. The population in this study was the State Civil Apparatus of Situbondo Resort Police. The sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this research used the Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that motivation has a positive but insignificant effect on job satisfaction, work discipline has a positive but insignificant effect on job satisfaction, leadership has a positive significant effect on job satisfaction, motivation has a positive significant effect on performance, work discipline has a positive but insignificant effect to performance, leadership has a positive but insignificant effect on performance, job satisfaction has a positive significant effect on performance. The results of the indirect effect hypothesis test show that motivation has a positive but insignificant effect on performance through job satisfaction, work discipline has a positive but insignificant effect on performance through job satisfaction, while leadership has a significant positive effect on performance through job satisfaction.